Pengolahan Sampah Organik dengan Menggunakan Compost Bag di Lingkungan Universitas Pendidikan Mandalika - Husnul Jannah; Baiq Muli Harisanti; Iwan Desimal; Sri Nopita Primawati; Dina Zurriyatun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The purpose of this community service activity is to introduce and train Indonesian New Generation students (recipients of a scholarship from Bank Indonesia) at Mandalika University of Education, Mataram, West Nusa Tenggara Province in processing organic waste into compost through fermentation with the help of effective microorganism (EM4) as a bioactivator. The stages of this service activity are: 1) introduction; 2) practice activities for the initial process of fermentation; and 3) follow-up activities (observation for 2 months). The 1 day activity is used to process organic waste in the form of dry and wet leaves, then chopped into smaller pieces so that it decomposes more quickly, then fermented using EM4 as a bioactivator (observations after 2 months). Compost fermentation takes at least 2 months to get better results, taking into account the factors that affect composting, including: C/N (Carbon/Nitrogen) ratio, aeration, porosity, humidity, temperature, acidity level (pH), nutrient content, hazardous material content, and composting time. Based on the results of the activity evaluation, it can be concluded that the objectives of this community service activity have been achieved as expected. This achievement can be seen from the ability of students to process organic waste into compost which is ready to be used as fertilizer for plants.